Young Fu of the upper Yangtze - Lewis, Elizabeth Foreman 1892-1958.; Young, Ed. (New York Dell Publishing, 1973)
In the 1920's a Chinese youth from the country comes to Chungking with his mother where the bustling city offers adventure and his apprenticeship to a coppersmith brings good fortune.
Keywords: City and town life -- Fiction. -- China; China -- Fiction; China -- Fiction